2009
DOI: 10.1016/j.bcp.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

S-adenosylmethionine regulates thiopurine methyltransferase activity and decreases 6-mercaptopurine cytotoxicity in MOLT lymphoblasts

Abstract: Six-mercaptopurine (6-MP) is a pro-drug widely used in treatment of various diseases, including acute lymphoblastic leukaemia (ALL). Side-effects of thiopurine therapy have been correlated with thiopurine methyltransferase (TPMT) activity. We propose a novel TPMT-mediated mechanism of S-adenosylmethionine (SAM)-specific effects on 6-mercaptopurine (6-MP) induced cytotoxicity in a model cell line for acute lymphoblastic leukemia (MOLT). Our results show that exogenous SAM (10-50microM) rescues cells from the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…A study by Brouwer et al 2005 [15], showed that TPMT enzyme activity increased in MOLT4 cells after incubation with MTX, however, in their study, cells were simultaneously treated with methionine, thus creating increased amounts of SAM in the cells. As SAM stabilises TPMT it could be that the increase in enzyme activity is due to SAM, not to MTX [21].…”
Section: In Vivo and In Vitro Effects Of Mtx On Tpmt And 6-mp Metabolmentioning
confidence: 99%
“…A study by Brouwer et al 2005 [15], showed that TPMT enzyme activity increased in MOLT4 cells after incubation with MTX, however, in their study, cells were simultaneously treated with methionine, thus creating increased amounts of SAM in the cells. As SAM stabilises TPMT it could be that the increase in enzyme activity is due to SAM, not to MTX [21].…”
Section: In Vivo and In Vitro Effects Of Mtx On Tpmt And 6-mp Metabolmentioning
confidence: 99%
“…We herein present evidence of a novel TPMT-mediated mechanism of SAM-specific effects on 6-MP-induced cytotoxicity [2]. Our results show that exogenous SAM rescues cells from the toxic effects of 6-MP by restoring cell proliferation and delaying the onset of apoptosis.…”
Section: Resultsmentioning
confidence: 88%
“…The importance of studying the influence of SAM on TPMT on a molecular level becomes even more clear by the fact that studies on cultured leukemic cells show that the cytotoxic effect of 6-MP can be reduced by the addition of exogenous SAM. The addition of exogenous SAM lowered the concentration of TGNs and methyl thioinosine monophosphate (MeTIMP)23, cytotoxic metabolites of 6-MP. In the same study, the addition of exogenous SAM reversed the 6-MP induced reduction of TPMT activity and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding that polymorphisms in the methylene tetrahydrofolate reductase (MTHFR) gene could indirectly influence TPMT activity22, by altering intracellular SAM levels as a result of the affected folate metabolism, leads to the question of whether SAM could function as a predictor of the enzymatic activity. By studying SAM levels and TPMT activity in a leukemic cell line, it has been shown that adding exogenous SAM to culturing media could sustain the intracellular levels of adenosine triphosphate (ATP) and SAM and delay the cytotoxic mechanisms, induced by 6-MP23. Earlier studies comparing the intrinsic stability, at 37 °C, of TPMT*1, TPMT*3B and TPMT*3C revealed that, despite the fact that no loss of immunodetectable protein occurred, the addition of SAM partially stabilized the catalytic activity of TPMT*3C24.…”
mentioning
confidence: 99%